Appraisal of socioeconomic factors that influence the adoption of green-water technology in prawn grow-out culture in Negros Occidental. - Hembra, Sheila S.
The decision of adopting a new technology, provided it is widely acceptable and largely beneficial, is one key factor to economic growth and development. Pertinent to the choice of adopting a newly introduced technology are factors which affect decision and which have to be considered. Understanding the choice of adoption and the factors that influenced it is essential for biological scientists who had designed the technology. More often socioeconomic factors and other related variables are neglected in the design of the technology. In considering the variables that were ascertained to have influenced the decision of adoption, corrective measures could be addressed by biological scientists to the failures of the design, and thus redesigning a technology to make it socially acceptable and appreciated by farmers., The data are largely qualtitative and gathered through reconnaissance and scheduled interviews with prawn operators, farm managers and all those who are involved in the prawn industry. The assessment of the data revealed the variables, other than the cost of technology, which had led to adoption. Personal variables include the education and literacy of prawn operators on prawn culture, experience in business, diversified sources of income and prawn operator's attitude towards risks. The factors that fall under situational variables further affects personal variables and these are the farm size, kinship and access to information, inputs, market and credit. The external variables could also alter decision to adopt and these identified as services provided by the cooperative and availability of inputs - bangus or tilapia to production.